Reduced ER-mitochondrial contact sites and mitochondrial Ca2+ flux in PRKN-mutant patient tyrosine hydroxylase reporter iPSC lines - Yokota, Mutsumi; Yoshino, Yutaro; Hosoi, Mitsuko; Hashimoto, Ryota; Kakuta, Soichiro; Shiga, Takahiro; Ishikawa, Kei-Ichi; Okano, Hideyuki; Hattori, Nobutaka; Akamatsu, Wado; Koike, Masato (Frontiers in Cell and Developmental Biology, 2023)
Endoplasmic reticulum-mitochondrial contact sites (ERMCS) play an important role in mitochondrial dynamics, calcium signaling, and autophagy. Disruption of the ERMCS has been linked to several neurodegenerative diseases, including Alzheimer’s disease (AD), Parkinson’s disease (PD), and amyotrophic lateral sclerosis (ALS). However, the etiological role of ERMCS in these diseases remains unclear. We previously established tyrosine hydroxylase reporter (TH-GFP) iPSC lines from a PD patient with a PRKN mutation to perform correlative light-electron microscopy (CLEM) analysis and live cell imaging in GFP-expressing dopaminergic neurons. Here, we analyzed ERMCS in GFP-expressing PRKN-mutant dopaminergic neurons from patients using CLEM and a proximity ligation assay (PLA). The PLA showed that the ERMCS were significantly reduced in PRKN-mutant patient dopaminergic neurons compared to the control under normal conditions. The reduction of the ERMCS in PRKN-mutant patient dopaminergic neurons was further enhanced by treatment with a mitochondrial uncoupler. In addition, mitochondrial calcium imaging showed that mitochondrial Ca2+ flux was significantly reduced in PRKN-mutant patient dopaminergic neurons compared to the control. These results suggest a defect in calcium flux from ER to mitochondria is due to the decreased ERMCS in PRKN-mutant patient dopaminergic neurons. Our study of ERMCS using TH-GFP iPSC lines would contribute to further understanding of the mechanisms of dopaminergic neuron degeneration in patients with PRKN mutations.